Prevalence of HLA-B27, clinical characteristics and treatment outcomes in children with enthesitis-related arthritis - Boonsiri Jittawattanarat; Sirirat Charuvanij; Sirikarn Tangcheewinsirikul; Maynart Sukharomana (BMC, 2024)
Abstract Background Enthesitis-related arthritis (ERA) is a subtype of juvenile idiopathic arthritis with high disease burden. The objectives of this study were to explore the prevalence of HLA-B27, clinical characteristics, and treatment outcomes in children with ERA and compare the differences between HLA-B27 positive and negative patients. Methods A retrospective cohort study at a pediatric rheumatology clinic in a tertiary referral hospital in Bangkok, Thailand, including ERA patients with at least 6 months of follow-up (July 2011-April 2022) was performed. Data were collected from medical records from diagnosis to recent follow-up, assessing disease activity and treatment outcomes, with an analysis comparing HLA-B27 positive and negative patients. Descriptive statistics were used for data analysis. Results There were 59 ERA patients with mean age ± SD at diagnosis 11.2 ± 2.5 years, 53 males (89.8%), and positive HLA-B27 in 38 patients (64.4%). The HLA-B27 positive group had significantly higher levels of inflammatory markers at initial diagnosis (p = 0.001), lower baseline hemoglobin (p = 0.001) and hematocrit (p = 0.002), higher disease activity assessed by the Juvenile Spondyloarthritis Disease Activity score at 6 and 12 months of follow-up (p = 0.028 and 0.040, respectively), increased utilization of bridging systemic corticosteroids (60.5% vs. 14.3%, p = 0.001) and anti-TNF (39.5% vs. 9.5%, p = 0.018), and longer duration of methotrexate (median[IQR] 1.7[1.1-3.1] vs. 1.3[0.6-1.9] years, p = 0.040). The HLA-B27 negative group had more prevalent hip arthritis than the positive group at initial diagnosis (66.7% vs. 28.9%, p = 0.005) and during the course of the disease (71.4% vs. 36.8%, p = 0.011). Conclusion Most of the ERA patients tested positive for HLA-B27. Throughout the follow-up period, these patients demonstrated greater disease activity, greater use of corticosteroids and anti-TNF, and longer duration of methotrexate to control the disease.